Innovative moments and poor outcome in narrative therapy - Santos, Anita (2011)
Aims: To analyze a poor outcome case of narrative therapy with a woman victim of intimate violence. Method: The Innovative Moments Coding System: version 1 was applied to all sessions to track the innovative moments (i-moments) in the therapeutic conversation. I–moments are the narrative details that occur in psychotherapeutic conversations that are outside the influence of the problematic narrative. This research aims to describe the processes involved in meanings’ stability along psychotherapy through a dialogical approach to meaning making. Results: Contrarily to what usually occurs in good outcome cases, re-conceptualization i-moments are absent. Moreover, two specific types of i-moments emerged with higher duration: reflection and protest. Qualitative analysis showed that the potential meanings of these i-moments were surpassed by a return to the problematic narrative. Conclusion: The therapeutic stability seems to be maintained by a systematic return to the problematic narrative after the emergence of novelties, a process that was referred from a dialogical perspective as a mutual in-feeding of voices (Valsiner, 2002), one that emerges in the i-moment and another one that supports the problematic narrative. The problematic narrative is maintained by an oscillation between these two types of voices along therapy.